Association analysis of the gut microbiota in predicting outcomes for patients with acute ischemic stroke and H-type hypertension - Yu, Shicheng; Chen, Jiaxin; Zhao, Yiting; Liao, Xiaolan; Chen, Qionglei; Xie, Huijia; Liu, Jiaming; Sun, Jing; Zhi, Shaoce (Frontiers in Neurology, 2023)
Introduction: H-type hypertension (HHTN) is a subtype of hypertension, which is prone to aggravate the prognosis of acute ischemic stroke (AIS). Recent studies have highlighted the vital role of gut microbiota in both hypertension and AIS, but there is little available data on the relationship between gut microbiota and the progression of AIS patients with HHTN. Here, we investigated the microbial signature of AIS patients with HHTN and identified characteristic bacteria as biomarkers for predicting prognosis. Methods: AIS patients with HHTN (n = 150) and without HHTN (n = 50) were enrolled. All patients received modified Rankin Scale (mRS) assessment at 3 months after discharge. Fecal from the participants, including 150 AIS patients with HHTN, 50 AIS patients with non-HHT and 90 healthy subjects with HHTN, were collected at time of admission and determined by 16s rRNA sequencing to characterize the bacterial taxa, predict function, and conduct correlation analysis between specific taxa and clinical features. Results: Our results showed that the composition of gut microbiota in HHTN patients differed significantly from that in non-HHTN patients. The abundance of genus Bacteroides, Escherichia-Shigella, Lactobacillus, Bifidobacterium and Prevotella in AIS patients with HHTN were significantly increased compared to AIS patients without HHTN, while the genus Streptococcus, Faecalibacterium and Klebsiella were significantly decreased. Meanwhile, Bacteroides, Lactobacillus, Bifidobacterium and Klebsiella in AIS patients with HHTN were enriched than healthy subjects with HHTN, while Escherichia-Shigella, Blautia and Faecalibacterium were less. Moreover, Butyricicoccus, Rothia and Family_XIII_UCG-001 were negatively connected with NIHSS score, as well as genera (Butyricicoccus and Rothia) were observed negatively associated with mRS score. Butyricicoccus, Romboutsia and Terrisporobacter, were associated with poor prognosis, whereas the increase of Butyricimonas and Odoribacter, were correlated to good outcomes. Generated by eight genera and clinical indexes, the area under the curve (AUC) value of receiver operating characteristic (ROC) curve achieved 0.739 to effectively predict the prognosis of AIS patients with HHTN. Conclusions: These findings revealed the microbial signature of AIS patients with HHTN, and further provided potential microbial biomarkers for clinical diagnosis of AIS patients with HHTN.